United Kingdom : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
The United Kingdom showed impressive economic performance and low inflation owing to its strong policy frameworks. Executive Directors commended this development, and stressed the need to tighten fiscal and monetary stances, and accelerate structural reforms. They appreciated the steps to increase competition, encourage innovation, and put in place appropriate regulatory regimes. Directors welcomed the recent welfare and labor market reforms. They agreed that the entry into European Economic and Monetary Union remains a key medium-term decision for the country.